HUBUNGAN SANITASI RUMAH SAKIT DENGAN JUMLAH KUMAN UDARA DI RUANG RAWAT INAP RUMAH SAKIT NASIONAL DIPONEGORO SEMARANG - Apriliana, Indah; Martini, Martini; Kusariana, Nissa; Udiyono, Ari (Fakultas Kesehatan Masyarakat, 2019)
Air pollution in a room is 1000 times more dangerous than pollution of air outside the room because it can have a negative impact on human health. The treatment room have a risk for patients, medical / non-medical workers, and visitors to be infected. This statement is based on the results of the initial laboratory examinations of researchers in certain treatment rooms that found microbes in the RSND treatment room. The purpose of this study was to analyze the relationship between hospital sanitation (temperature, humidity, lighting, occupancy density) and the number of air germs in the RSND. This research is observational research with the cross-sectional approach. The sample of the reseach is 40 treatment rooms. The test results showed that there was no significant relationship between hospital sanitation (temperature, humidity, lighting and occupancy density) and the number of air germs (p = 0.542, p = 0.218, p = 0.082, p = 0.317).